Pleasure factory : horrors of the Singapore flesh trade - Leong, Kai Wen (Marshall Cavendish Editions, 2013)
Underneath Singapore's squeaky-clean exterior is a dark realm like no other. Based on interviews with hundreds of prostitutes in Singapore and years of research, we bring you Pleasure Factory. In the Pleasure Factory, women advertise pleasure by the hour, but the only real product is pain. Night after night, these women force smiles onto their faces, while their bodies are taken, ravaged, and violated. Day after day, they force themselves to continue for the sake of their children, families, for sheer desperate human survival. The only defense is numbness. The only comfort is empty hope. But w.